Drug- Related Problem (Drps) pada Pasien Pediatric dengan Tuberculosis: Systematic Review - Meia Yevi Setiawati; Zakky Cholisoh (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Drug-Related Problems (DRPs) are a common issue in the treatment of childhood tuberculosis due to the complexity of treatment regimens, the long duration of therapy, and the immature physiological condition of children. The occurrence of DRPs has the potential to reduce treatment success and increase the risk of side effects and drug resistance. Objective: To systematically review the incidence, types, severity, and risk factors of DRPs in pediatric patients with tuberculosis. Methods: This systematic review was compiled based on the Preferred Reporting Items For Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A literature search was conducted thru the PubMed, ScienceDirect, and Google Scholar databases for publications from the past 15 years. The included studies involved pediatric patients aged 0–18 years and reported data related to DRPs, primarily Adverse Drug Reactions (ADRs). Data analysis was conducted descriptively and narratively. Results: A total of 6 studies met the inclusion criteria. The prevalence of DRPs in children with tuberculosis ranges from 13.2% to 44.7%. The most frequently reported type of DRP is Adverse Drug Reactions (ADRs), particularly gastrointestinal disorders and hepatotoxicity. Most DRPs are classified as mild to moderate. The main risk factors for DRP include poor nutritional status, lack of patient or parent education, high-dose use without individual adjustment, and the use of combination drugs. Some studies report that educational interventions can improve adherence and reduce the incidence of DRP. Conclusion: Drug-related problems (DRPs) in children remain a serious challenge in the treatment of tuberculosis in children. Increased therapy monitoring, patient and family education, and clinical pharmacist involvement are essential for effectively preventing and managing DRPs to improve therapeutic outcomes. Keywords: Tuberculosis, Children, Drug-Related Problems, Adverse Drug Reactions, Anti-Tuberculosis Drugs.  ABSTRAK Drug-Related Problems (DRPs) merupakan permasalahan yang sering terjadi pada terapi tuberkulosis anak akibat kompleksitas regimen pengobatan, durasi terapi panjang, dan kondisi fisiologis anak yang masih berkembang. Kejadian DRPs berpotensi menurunkan keberhasilan terapi dan meningkatkan risiko efek samping serta resistensi obat. Tujuan: Meninjau secara sistematis kejadian, jenis, tingkat keparahan, dan faktor risiko DRPs pada pasien anak dengan tuberkulosis.  berpotensi menurunkan keberhasilan terapi. Metode:Tinjauan sistematis ini disusun berdasarkan pedoman Preferred Reporting Items For Systematic Reviews and Meta-Analyses (PRISMA). Pencarian literatur dilakukan melalui basis data PubMed, ScienceDirect, dan Google Scholar untuk 15 tahun terakhir. Artikel yang disertakan melibatkan pasien anak berusia 0–18 tahun dan melaporkan data terkait DRPs, terutama adverse drug reactions (ADR). Analisis data dilakukan secara deskriptif naratif. Hasil: Sebanyak 6 artikel memenuhi kriteria inklusi. Prevalensi DRPs pada anak dengan tuberkulosis berkisar antara 13,2% hingga 44,7%. Jenis DRPs yang sering dilaporkan yaitu Adverse Drug Reactions (ADR) terutama gangguan saluran cerna dan hepatotoksisitas. Sebagian besar DRPs diklasifikasikan sebagai ringan hingga sedang. Faktor risiko utama DRPs meliputi status gizi buruk, kurangnya edukasi pasien atau orang tua, penggunaan dosis tinggi tanpa penyesuaian individual, dan terapi kombinasi obat. Beberapa artikel melaporkan bahwa intervensi edukatif dapat meningkatkan kepatuhan dan menurunkan kejadian DRPs. Kesimpulan:Drug-Related Problems (DRPs) pada anak masih menjadi tantangan serius dalam terapi tuberkulosis pada anak. Peningkatan pemantauan terapi, edukasi pasien dan keluarga, serta keterlibatan apoteker klinis sangat diperlukan untuk mencegah dan mengelola DRPs secara efektif guna meningkatkan keberhasilan terapi.  Kata Kunci: Tuberkulosis, Anak, Drug-Related Problems, Adverse Drug Reactions, Obat Anti-Tuberkulosis.